Thrombospondin-1 Serum Levels In Hypertensive Patients With Endothelial Dysfunction After One Year Of Treatment With Perindopril - Buda V; Andor M; Cristescu C; Tomescu MC; Muntean DM; Bâibâță DE; Bordejevic DA; Danciu C; Dalleur O; Coricovac D; Crainiceanu Z; Tudor A; et al. (Dove Medical Press, 2019)
Valentina Buda,1,* Minodora Andor,2,* Carmen Cristescu,1,* Mirela Cleopatra Tomescu,2 Danina M Muntean,3 Dana Emilia Bâibâță,4,5 Diana Aurora Bordejevic,4,5 Corina Danciu,6 Olivia Dalleur,7 Dorina Coricovac,8 Zorin Crainiceanu,9 Anca Tudor,10 Ionut Ledeti,11 Lucian Petrescu4,5 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, “Victor Babeş” University of Medicine and Pharmacy, Timisoara 300041, Romania; 2Department of Medical Semiotics, Faculty of Medicine, “Victor Babeş” University of Medicine and Pharmacy, Timisoara 300041, Romania; 3Department of Pathophysiology, Faculty of Medicine, “Victor Babeş” University of Medicine and Pharmacy, Timisoara 300041, Romania; 4Department of Cardiology VI, Faculty of Medicine, “Victor Babeş” University of Medicine and Pharmacy, Timisoara 300041, Romania; 5Cardiovascular Diseases Institute, Timisoara 300310, Romania; 6Department of Pharmacognosy, “Victor Babeş” University of Medicine and Pharmacy, Timisoara 300041, Romania; 7Clinical Pharmacy Research Group, Louvain Drug Research Institute, Université Catholique De Louvain, Woluwe-Saint-Lambert 1200, Bruxelles, Belgium; 8Department of Toxicology, Faculty of Pharmacy, “Victor Babeş” University of Medicine and Pharmacy, Timisoara 300041, Romania; 9Department of Plastic and Reconstructive Surgery, Faculty of Medicine, “Victor Babeş” University of Medicine and Pharmacy, Timisoara 300041, Romania; 10Department of Statistics and Biomedical Informatics, Faculty of Medicine, “Victor Babeş” University of Medicine and Pharmacy, Timisoara 300041, Romania; 11Department of Physical Chemistry, Faculty of Pharmacy, “Victor Babeş” University of Medicine and Pharmacy, Timisoara 300041, Romania*These authors contributed equally to this workCorrespondence: Valentina BudaCorina Danciu Faculty of Pharmacy, “Victor Babeş” University of Medicine and Pharmacy, 2 Eftimie Murgu Street, Timisoara 300041, RomaniaTel +40-256-494-604Fax +40-256-494-604Email buda.valentina.oana@gmail.comBackground: Thrombospondin-1 (TSP-1) is a matricellular functional protein of the extracellular matrix. As it is not constitutively present extracellularly, its secretion is enhanced in several situations, namely injury, chronic pathology, tissue remodeling, angiogenesis, and aging. Over the last decade, TSP-1 has been reported to be involved in complex and opposing biological effects on vasculature in the context of NO signaling. Several studies have reported high patient TSP-1 plasma levels, indicating that the protein can potentially serve as a prognostic marker for pulmonary arterial hypertension.Materials and methods: Here, we aimed to quantify TSP-1 serum levels in hypertensive patients with endothelial dysfunction before and after one year of treatment with Perindopril (an antihypertensive drug with vasoprotective properties).Results: After one year of treatment, TSP-1 levels increased in hypertensive patients compared to baseline (T0: 8061.9 ± 3684.80 vs T1: 15380±5887 ng/mL, p<0.001) and compared to non-hypertensive controls (9221.03 ± 6510.21 ng/mL). In contrast, pentraxin-3 plasma levels were decreased after one year of Perindopril treatment in both hypertensive (T0: 0.91 ± 0.51 vs T1: 0.50 ± 0.24 ng/mL, p<0.001) and control group (1.36 ±1.5 ng/mL) patients, although flow-mediated vasodilation and intima-media thickness assessment parameters were not significantly changed. Systolic and diastolic blood pressure values as well as levels of fibrinogen, high-sensitivity C-reactive protein, triglycerides, and alanine aminotransferase were found to be significantly lower after one year of treatment with Perindopril. High levels of TSP-1 strongly correlated with platelet count (positive), lymphocytes (positive), red cell distribution width-CV (positive), systolic blood pressure (negative), and mean corpuscular hemoglobin (negative) after one year of treatment. Blood urea nitrogen was found to be a protective factor for TSP-1, while glucose and heart rate were found to be risk factors prior to and after treatment.Keywords: TSP-1, essential arterial hypertension, endothelial function, ACE inhibitors